When Should Sarcoidosis Be Treated? - Young, Roscoe C. (1986)
About 80 percent of sarcoidosis cases are benign and do not require treatment, but 20 percent will have chronic unremitting disease for which therapy is essential. It is important that the physician identify this group and begin therapy promptly. If the disease is active, treat. If it is inactive, do not treat. Activity depends upon three major tests: serum angiotensin converting enzyme, gallium 67 scan, and bronchoalveolar lavage. The other consideration is involvement of vital organ systems; ie, active ocular disease, progressive pulmonary involvement as evidenced by increasing symptoms, impaired and deteriorating pulmonary function, or radiographic changes; hypercalcemia or hypercalciuria; central nervous system involvement; disfiguring cutaneous lesions; and myocardial sarcoidosis. Following a therapeutic decision to treat, adrenocorticoids are the drugs of choice. Methylprednisolone, prednisone, and cortisol are listed in order of benefit. Alternate day and/or low-dose steroids are increasing in popularity. Chloroquine phosphate is beneficial for skin lesions, while oxyphenbutazone has been found to be at least as effective as prednisone. Immunosuppressives may be used also. Chlorambucil and azathioprine have shown variable results. Cyclosporine (Cyclosporin A) shows promise and is now undergoing therapeutic trials.